EVALUASI PROGRAM KOTA LAYAK ANAK DALAM UPAYA PEMENUHAN HAK ANAK DALAM KLASTER PENDIDIKAN, PEMANFAATAN WAKTU LUANG, DAN KEGIATAN BUDAYA DI KOTA SERANG - Shelvy, Shelvy Hendianingsih; Suwaib Amirudin; Ayuning Budiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The city of Serang faces significant challenges in realizing a Child Friendly City, even though it involves various parties, problems such as violence against children, dropping out of school, and low access to education still hinder the optimal fulfillment of children's rights. This research uses descriptive qualitative methods to evaluate Serang City Regional Regulation Policy No. 06 of 2015 concerning Children-Friendly Cities, with a focus on describing phenomena related to the fulfillment and protection of children's rights in the city. Through systematic data analysis and source triangulation, this research aims to ensure the credibility and objectivity of the findings obtained. This research shows that the Child Friendly City (KLA) program in Serang City, especially in the Education, Utilization of Free Time and Cultural Activities clusters, still faces various challenges in fulfilling children's rights, with very low participation rates for children returning to school and a lack of facilities. as well as adequate socialization. Collaborative efforts between the government and the community are needed to increase program effectiveness and ensure children's rights are optimally fulfilled.